Keterkaitan agama dengan upaya self healing - Khoirotunnisa, Siti Safira (Maliki Interdisciplinary Journal, 2024)
The purpose of this research is to identify the relationship between religion and self-healing efforts, analyzed through the perspectives of the Qur'an, psychology, and health aspects. With a focus on the following research areas: 1) The principles of self-healing in the field of psychology. 2) How the correlation between religion and self-healing is perceived within the realms of health science and psychology. The methodology employed in this study involves referring to scholarly works which are subsequently reflected upon real-life occurrences. Data collection is carried out by examining the contextual interpretation of the concept of self-healing within religious studies and investigating how this concept can be applied in relation to psychological and health theories. There are three ways of self-healing related to religion that can be applied, including: self-acceptance, engaging in positive self-talk or prayer, and cultivating gratitude.